Helix 2 of the paired domain plays a key role in the regulation of DNA-binding by the Pax-3 homeodomain. - Fortin, A S (1998)
Pax3 contains two structurally independent DNA-binding domains, a paired domain (PD) and a homeodomain (HD). Biochemical and mutagenesis studies have shown that both domains are functionally interdependent. In particular, it has been shown that the PD can regulate the DNA-binding specificity and dimerization potential of the HD. To delineate Pax3 protein segments that are involved in the regulation of HD DNA-binding, a series of chimeric proteins were created in which the HD and linker region were gradually replaced with corresponding sequences from a heterologous HD protein, Phox. Characterization of chimeric proteins by electrophoretic mobility shift analysis (EMSA) suggests that a portion of the linker region contributes to the functional interaction between the PD and HD. In addition, stepwise removal of sequences from the Pax3 PD was used to define regions within this domain that are involved in the regulation of HD DNA-binding. EMSA of these proteins in the context of the chimeric Pax3/Phox backbone provided two key findings: (i) the C-terminal subdomain of the PD does not play a major role in the regulation of HD DNA-binding and (ii) the N-terminal subdomain and, in particular, the second alpha-helix are essential for modulation of HD DNA-binding. Significantly, deletion of helix 2 was found to be sufficient to uncouple regulation of HD DNA-binding by the PD.